Participating for Profit: Bilateral-Multilateral Nexus in Indonesian Foreign Policy in the Era of Joko Widodo (2014-2019) - Rosyidin, Mohamad; Kusumawardhana, Indra (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
This paper  seeks  to  analyze  Indonesia’s  multilateral  diplomacy  under  President  Joko  Widodo (Jokowi)during his first term of presidency(2014-2019). Specifically, this research will be focusing on threemultilateral forums; G20, APEC, and East Asia Summit. Thispaper departs from the puzzle of why Jokowi’s foreign policy seems to be paradoxical; on one hand, the bilateral approach looks very prominent but on the other, Jokowi does not seem to be very keen in engaging in multilateral forums. Using  bilateral-multilateral  nexus,  this  paper  argues  that  Indonesia’s  participation  in  multilateral forums  is  only  intended  as  a  means  of  pursuing  short-term  interests  rather  than  to  contributing  to global  norms.  Jokowi  uses  multilateralism  just  as  a  venue  to  arrange  further bilateral  cooperation with potential partners.